The effect of Ferralsol mineralogy on the distribution of organic C across aggregate size fractions under native vegetation and no-tillage agriculture - Maltoni, K. L. [UNESP]; De Mello, L. M.M. [UNESP]; Dubbin, W. E. (Wiley, 2017)
No-tillage management can increase soil surface layer organic C (OC) levels compared with conventional tillage. The mechanisms underlying this increase in highly weathered tropical soils, such as Ferralsols, are not well established. The objective of this study was therefore to evaluate the influence of mineralogy on aggregation and the apportionment of OC across aggregate size fractions in a Brazilian Ferralsol under native vegetation (NV) and no-tillage management for 10 (NT10) or 20 (NT20) yrs. Under native vegetation, soil OC generally increased with increasing aggregate size while, in response to changing management, soil OC increased in the order NT10 (8.8 g/kg) < NT20 (12.7 g/kg) < NV (19.1 g/kg). There were no significant differences in the mineralogy of the clay size fractions among the three treatments, with the notable exception of the CBD-extractable Fe oxide fraction (FeCBD). The FeCBD fraction comprises various pedogenic Fe(hydr)oxides and increased from NT10 (33.9 g/kg) to NT20 (64.2 g/kg). The OC/FeCBD mass ratio within aggregates increased in the order NT10 < NT20 < NV while R2 values for OC and FeCBD occurrence follow this same trend, with the NT10 soil showing a weaker correlation (R2 = 0.178) compared with the NV soil (R2 = 0.533). We propose that formation of organo-Fe(III) oxide associations is promoted with implementation of NT management and the consequent reduction in macroaggregate turnover. The development of the OC-Fe(III) oxide associations and their evolution over time within aggregates to more thermodynamically stable entities will strongly influence the long-term preservation of soil OC.
Keywords: aggregation; carbon; Ferralsol; iron oxide; mineralogy